2016
DOI: 10.1177/0960327116658108
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of ceftriaxone- and cefotaxime-induced biliary pseudolithiasis or nephrolithiasis: A prospective study in 154 children

Abstract: Background: Biliary lithiasis, or sludge, and nephrolithiasis have been reported as a possible complication of ceftriaxone therapy. However, no study related to cefotaxime-induced biliary pseudolithiasis or nephrolithiasis was observed in the literature. Therefore, we investigated the comparative formation of biliary pseudolithiasis and nephrolithiasis after cefotaxime and ceftriaxone therapies. Methods: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 18 publications
1
17
0
3
Order By: Relevance
“…Concurrent use of intravenous ceftriaxone and calcium-containing solutions in neonates and young infants has been associated with calcium precipitation. Biliary pseudolithiasis and urolithiasis have also been reported in paediatric patients 6 7. There is a lack of overall assessment of the safety of ceftriaxone, one of the most widely used antibiotics in paediatric patients.…”
Section: Introductionmentioning
confidence: 99%
“…Concurrent use of intravenous ceftriaxone and calcium-containing solutions in neonates and young infants has been associated with calcium precipitation. Biliary pseudolithiasis and urolithiasis have also been reported in paediatric patients 6 7. There is a lack of overall assessment of the safety of ceftriaxone, one of the most widely used antibiotics in paediatric patients.…”
Section: Introductionmentioning
confidence: 99%
“…Данный факт соответствует исследованию, проведен-ному Lokman Ustoyl и соавт. [10], в результате которого авторы установили, что у детей старше 4,5 года значи-тельно возрастает риск развития ЦИБПЛ. По гендер-ному признаку отличий не наблюдалось (мальчиков -50 %, девочек -50 %).…”
Section: результаты и обсуждениеunclassified
“…Данный феномен полу-чил название «цефалоспорининдуцированный били- арный псевдолитиаз» (ЦИБПЛ). Билиарный сладж чаще развивается на фоне применения цефтриаксона (15-57 %) [6,7,9], но встречается и при использова-нии цефотаксима (5,9 %) [10] и цефтазидима (2 %) [11]. Считалось, что формирование преципитатов в поло-сти желчного пузыря на фоне применения цефтри-аксона носит исключительно транзиторный характер [6,7], однако результаты исследований последних лет опровергают абсолютную обратимость ЦИБПЛ.…”
Section: Introductionunclassified
“…In 1988, Schaad et al [26] reported the first case of ceftriaxone-induced nephrolithiasis in one child out of 37 children. Soon after that, several authors reported crystalluria [27,28], hypercalciuria [29,30] and urolithiasis [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] in children following ceftriaxone use. It is considered the most common lithogenic antibacterial drug in the pediatric population, with an incidence ranging from 0.6% [45] to 8.3% [31].…”
Section: Ceftriaxonementioning
confidence: 99%
“…Cefotaxime is also a third-generation cephalosporin similar to ceftriaxone. Ustyol et al [38] compared the rate of biliary pseudolithiasis and nephrolithiasis between children using ceftriaxone and cefotaxime in the management of acute bacterial infection, showing no significant difference between these drugs in regard to drug-induced nephrolithiasis (1.2% vs 1.5%, p > 0.05). This is the only report in the literature about cefotaxime-induced nephrolithiasis in the pediatric population, and further studies are required to confirm the lithogenic effect of this antibacterial drug.…”
Section: Metabolically Drug-induced Nephrolithiasismentioning
confidence: 99%